2010
DOI: 10.1016/j.hrthm.2010.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-function mutation S422L in the KCNJ8-encoded cardiac KATP channel Kir6.1 as a pathogenic substrate for J-wave syndromes

Abstract: Background-J Wave Syndromes have emerged conceptually to encompass the pleiotropic expression of J point abnormalities including Brugada syndrome (BrS) and early repolarization syndrome (ERS). Recently, KCNJ8, which encodes the cardiac K ATP Kir6.1 channel, has been implicated in ERS following the identification of a functionally uncharacterized missense mutation, S422L. Here, we sought to further explore KCNJ8 as a novel susceptibility gene for J wave syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
168
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 248 publications
(176 citation statements)
references
References 40 publications
3
168
1
4
Order By: Relevance
“…The WT- or N406K-SCN5A cDNA was transiently co-transfected with pMaxGFP cDNA, at a ratio of 5:1, into HEK293 cells with Superfect (Qiagen, Valencia, CA) following manufacturer’s recommended protocol [13,14]. After 3–5 hours of incubation, the transfection reagent-DNA mixture was replaced with 3 ml of normal culture medium with or without 500 μM mexiletine, and the cells were incubated at 37°C for 48 hours.…”
Section: Methodsmentioning
confidence: 99%
“…The WT- or N406K-SCN5A cDNA was transiently co-transfected with pMaxGFP cDNA, at a ratio of 5:1, into HEK293 cells with Superfect (Qiagen, Valencia, CA) following manufacturer’s recommended protocol [13,14]. After 3–5 hours of incubation, the transfection reagent-DNA mixture was replaced with 3 ml of normal culture medium with or without 500 μM mexiletine, and the cells were incubated at 37°C for 48 hours.…”
Section: Methodsmentioning
confidence: 99%
“…61 In a previous study, the mutation was shown to display a gain-of-function effect. 62 The KCNA5 gene encodes the atria-specific K v 1.5 channel responsible for the ultra-rapid delayed rectifier potassium current, I Kur , involved in cardiac repolarization. Olson et al 63 identified a nonsense mutation in a familial case of AF.…”
Section: Potassium Channel Mutationsmentioning
confidence: 99%
“…9,14 Mutations in glycerol-3-phophate dehydrogenase 1-like enzyme gene (GPD1L, BrS2), SCN1B (β1-subunit of Na channel, BrS5), KCNE3 (MiRP2; BrS6), SCN3B (β3-subunit of Na channel, BrS7), KCNJ8 (BrS8), and KCND3 (BrS10) are more rare. [10][11][12]15,16,34 These genetic defects cause a loss of function of I Na or I Ca , or a gain of function of I to . These and other genetic variants may give rise to subclinical forms of BrS, that can predispose to acquired forms of BrS developing following administration of antidepressants such as amitriptyline and pharmacological agents with similar actions.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations leading to loss of function in I Na and I Ca , as well as those giving rise to a gain of function in I to , have been identified as genetic causes of BrS. [6][7][8][9][10][11][12][13][14][15][16][17] BrS has thus far been associated with mutations in 11 different genes.…”
Section: Introductionmentioning
confidence: 99%